2006
DOI: 10.1177/155005940603700307
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Study of Learning-Disabled Children Treated with Neurofeedback or Placebo

Abstract: This report is a 2-year follow-up to a previous study describing positive behavioral changes and a spurt of EEG maturation with theta/alpha neurofeedback (NFB) training in a group of Learning Disabled (LD) children. In a control paired group, treated with placebo, behavioral changes were not observed and the smaller maturational EEG changes observed were easily explained by increased age. Two years later, the EEG maturational lag in Control Group children increased, reaching abnormally high theta Relative Powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 32 publications
3
45
0
2
Order By: Relevance
“…With regard to learning disabilities, Fernandez et al (2003) demonstrated in a placebocontrolled study that neurofeedback was an effective treatment, and the improvements were sustained on 2-year follow-up (Becerra et al, 2006). An additional report by Fernandez (Fernandez et al, 2007) on 16 children with learning disabilities documented significant EEG changes 2 months after neurofeedback compared to a placebo-control group where there were no EEG changes, and 10 of 11 children in the neurofeedback treatment group showed objective changes in academic performance compared with one in five children in the placebo group.…”
Section: Learning and Developmental Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to learning disabilities, Fernandez et al (2003) demonstrated in a placebocontrolled study that neurofeedback was an effective treatment, and the improvements were sustained on 2-year follow-up (Becerra et al, 2006). An additional report by Fernandez (Fernandez et al, 2007) on 16 children with learning disabilities documented significant EEG changes 2 months after neurofeedback compared to a placebo-control group where there were no EEG changes, and 10 of 11 children in the neurofeedback treatment group showed objective changes in academic performance compared with one in five children in the placebo group.…”
Section: Learning and Developmental Disabilitiesmentioning
confidence: 99%
“…It can be assumed that positive results from neurofeedback are due to a combination of expectancy (placebo) effects and effects specific to the neurofeedback treatment (Hammond, 2011;Perreau-Linck, Lessard, Levesque, & Beauregard, 2010), because placebo effects appear to be an active ingredient in virtually every therapeutic modality. We know, however, that there are improvements very specific to neurofeedback because there are several placebo-controlled studies that have demonstrated significant efficacious and specific effects beyond placebo influences in neurofeedback training (Raymond, Varney, et al, 2005), including with learning disabilities (Becerra et al, 2006;Fernandez et al, 2003), ADD=ADHD (deBeus & Kaiser, 2011;deNiet, 2011), anxiety (Raymond, Varney, et al, 2005), epilepsy (Lubar et al, 1981), sleep latency and declarative learning (Hoedlmoser et al, 2008), cognitive enhancement in the elderly (Angelakis et al, 2007), autism (Pineda et al, 2008), and depression (Choi et al, 2011), although one preliminary study did not find such effects (Lansbergen, van DongenBoomsma, Buitelaar, & Slaats-Willemse, 2010). Certainly animal studies (e.g., Sterman, 1973; also suggest that neurofeedback has therapeutic effects independent of placebo effects.…”
Section: Is More Placebo Controlled Research Needed?mentioning
confidence: 99%
“…Biofeedback is one of the few mind-body interventions that can potentially be blinded through the use of sham feedback. 45,46 Thus, placebo or expectancy effects which have a significant impact in many disorders are especially difficult to control for in mind-body clinical trials. 47,48 The potential benefit of a treatment in which the patient actively participates may be due to increased self-efficacy, the person's sense of ability to deal with a situation which, by itself, is associated with physiologic benefits.…”
Section: Placebo Effectsmentioning
confidence: 99%
“…První studii zjišťující efektivitu metody na děti s poruchami učení publikovali Fernández et al (2003), kontrolované studie provedli Becerra et al (2006) a Fernández et al (2007. Děti absolvovaly terapie na EEG biofeedbacku v rozmezí 20-35 sezení.…”
Section: Eeg Biofeedbackunclassified
“…Snížení pomalých frekvencí theta po 20 sezeních u experimentální skupiny potvrdila kontrolovaná studie (Fernández et al, 2003), která u kontrolní skupiny zhodnotila pouze snížení vln delta. Tyto výsledky byly potvrzeny i po dvou letech testování těchto dětí ve smyslu dalšího ubývání pomalých vln oproti kontrolní skupině, u které se nevyzrálost mozkové aktivity ještě prohloubila (Becerra et al, 2006). Na základě výsled-ků studií lze předpokládat dlouhodobé trvání navozených změn v mozkové aktivitě dětí.…”
Section: Diskuseunclassified